Pengaruh Karakteristik Wisatawan dan Motivasi Wisatawan terhadap Minat Berkunjung Kembali ke Petilasan Sri Aji Jayabaya Desa Menang Kabupaten Kediri - Dewi, Dini Kusuma; Estikowati, Estikowati; Astuti, Widji (University of Merdeka Malang, 2023)
Petilasan Sri Aji Jayabaya is one of the religious and cultural tourism destinations in Kediri Regency. The purpose of this study was to determine and analyze the influence of tourist characteristics and tourist motivation on tourists' intention to return. This research is an explanatory research, using quantitative research. The population in this study were tourists who had visited the Sri Aji Jayabaya tourist destination with a total sample of 99 respondents. Data collection techniques in this study used questionnaires and data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis testing. The results of this study indicate that the variable tourist characteristics partially has a significant effect on the intention to return variable, and the tourist motivation variable partially has a significant effect on the intention to return variable. The results of the analysis in this study also show that simultaneously the variables of tourist characteristics and motivation have a significant effect on the variable of intention to return.